Low-profile wideband unidirectional circularly polarized metasurface-based bowtie slot antenna - Nkimbeng, Cho Hilary Scott; Wang, Heesu; Park, Ikmo (IEEE Access, 2021)
In this paper, the design of a wideband circularly polarized (CP) bowtie slot antenna that uses metasurfaces is presented. The antenna consists of a single-layer substrate with the metasurface made of 4times4 periodic corner-truncated patches printed at the top side of the substrate and a bowtie-shaped slot etched on the ground plane. The metasurface made of corner-truncated patches are utilized to convert the linearly polarized wave into a CP wave. The antenna is fed by a 50- Omega coplanar waveguide. The antenna, with an overall size of 42 mm times42 mm times2.3 mm ( 0.71,,lambda _{mathrm {o}} times 0.71,,lambda _{mathrm {o}} times 0.038,,lambda _{mathrm {o}} at 5.1 GHz), was fabricated and measured. The measured reflection coefficient for vert textS_{11}vert < -10 dB yielded an impedance bandwidth of 3.75-6.67 GHz (55.7%), an axial ratio (AR) bandwidth of 4.38-5.98 GHz (31.37%), a 3-dB gain bandwidth of 3.75-6.0 GHz (46.88%), a peak gain of 7 dBic, and a high radiation efficiency of more than 93% within the AR bandwidth.
Keywords: Axial ratio bandwidth; Bow-tie slots; Bowtie slot antennas; Circularly-polarized; Corner-truncated patch; Lambda's; Low-profile; Metasurface; Single layer; Wide-band; Bowtie slot; Circular polarization; Low-profile; Metasurface; Slot antenna